Once in a full moon - Schreiber, Ellen (New York : Katherine Tegen Books, 2011)
Celeste Parker is unfazed by the werewolf stories commonly told in Legend's Run, but after a visit to a psychic Celeste encounters Brandon, a werewolf, with his pack and a kiss under the full moon is the beginning of a dangerous attraction.
Young Adult.
Young Adult
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Social classes -- Juvenile fiction; Supernatural -- Juvenile fiction; Werewolves -- Juvenile fiction; High schools -- Fiction; Schools -- Fiction; Social classes -- Fiction; Supernatural -- Fiction; Werewolves -- Fiction; High schools -- Fiction; School stories; Social classes -- Fiction; Supernatural -- Fiction; Werewolves -- Fiction